TEACHING COMPETENCE AND ROLE IN IMPROVING THINKING AIMED AT PRESERVING HEALTH IN STUDENTS - Ernazarov Abduvali Beknazarovich (The Conference Hub, 2025)
This article discusses about one of the important issues of thinking analysis which is the general and special competencies of the teacher of higher education in preserving the health of the student. This issue is relevant not only for specialists related to the basics of health, but also for all teachers. Teachers need to familiarize themselves with the principles, methods and techniques of health preservation pedagogy and apply them in educational activities.
Keywords: quality of education, educational process, goals, methodological approaches, basic skills, knowledge, teaching skills.